Identifying Drivers and Hindrances to the Disposal of Used Mobile Phones: A Study of User Behavior in the UAE - Gayle Patrao; Ajit Karnik (SAGE Open, 2023)
The use of mobile phones is ubiquitous around the world. Alongside the usage of mobile phones has been the rapid growth of related electronic waste, mainly aided by the very low rates of recycling of used phones. This study investigates the reasons behind the low rates of recycling of mobile phones in the United Arab Emirates, one of the heaviest users of mobile phones and one with very high e-waste generation. The study also has an important practical dimension in view of the policy initiative of the government in moving toward a circular economy. A significant contribution of this study is that we report the responses of phone users with respect to their usage patterns and factors that inhibit or enable them to recycle their phones. Our results show that environmental awareness about recycling and knowledge of the environmental consequences of improperly disposed of phones encourage recycling. However, personal, and external barriers prevent responsible disposal. We recommend strong government intervention, especially in school education, to enhance awareness about recycling. Further, the infrastructure for recycling needs to be made more user friendly and incentives should be offered to overcome personal barriers to recycling.